American nursing review for NCLEX-PN - Mourad, Leona A. (Springhouse, Pa. : Springhouse Corp., 1998)
This work has been updated to include Windows compatible software. It also includes topics on: pulse oximetry; accidental poisoning; diseases of major body systems; and fundamental nursing concepts and principles.
Includes bibliographical references and index.
Keywords: Practical nursing -- Examinations, questions, etc; National Council Licensure Examination for Practical/Vocational Nurses -- Study guides; Nursing, Practical -- examination questions